Digital marketing communication in improving consumer purchase decisions during the Covid-19 Pandemic - Dellaroza Geulis Sepliria; Indrawati Indrawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The COVID-19 pandemic in Indonesia impacted Small, Micro, and Medium Enterprises (MSMEs) entrepreneurs from various fields. Torch is one of them. At the start of the COVID-19 pandemic, Torch sales were down 50-80%. It is just that entering the middle of 2020, Torch managed to rise, and even its sales increased from the previous year. This is because of the digital marketing communications carried out. The purpose of this research is to find out how Torch's Digital Marketing Communication Improves Consumer Purchase Decisions, Especially During the COVID-19 Pandemic. This research was conducted using qualitative research methods with descriptive purposes based on the method. The strategy used is a case study. The sample selection technique in this study used purposive sampling and collection through interviews, observation, documentation and literature studies, and online searches. Interviews were conducted with ten informants on various criteria. The collected data is then validated by triangulation of sources and analyzed using an interactive model. The result of this research is that Torch has succeeded in increasing its business performance in the COVID -19 pandemic with digital marketing communication techniques through Search Engine Marketing (SEM), Online PR, Display Advertising, Email Marketing, and Social Media Marketing.